A preliminary study of the occurrence of Nematodes among goats in two farms in Kuantan - Jainul, Mohammed Abdullah; Mat Yusof, Afzan (2016)
The present study was performed as a preliminary study to determine the occurrence of gastrointestinal nematodes in two farms, Farm A and Farm B farm which both are located in Kuantan, Pahang. Present study also aims to identify the main genus of nematodes that predominantly infecting the goats as well as to identify the animal management systems as the possible factors of nematodes infections in the goats raised in the two farms. Methodology and results: Faecal samples were collected per rectum from 42 goats of both farms. Formal ether concentration technique and trichrome staining were performed to detect eggs of the nematodes under light microscope. Present result showed that there was occurrence of nematodes in goats reared in both farms. Present finding found that there was a significant difference (p= 0.014, p-value <0.05) in the occurrence of nematodes infections in goats from Farm A and Farm B whereby Farm A recorded higher occurrence (47.6%) as compared to Farm B (7.2%). In this study, among the genera of nematodes isolated from the goats were Heaemonchus, Trichostrongylus, Trichuris and Trichostronglus recorded highest prevalent among others. Conclusion, significance and impact of study: The difference in the occurrence of nematodes reported in goats from both farms is believed due to different management techniques implemented by each farm. To summarize, it is hoped that the results attained at the end of this study would facilitate evaluation of the occurrence level of parasites in goats in Kuantan.